Neurodevelopmental sequelae in premature newborns with extremely low weight and with very low weight at two years of age who left the Neonatal Intensive Care Unit of the Hospital Nacional Edgardo Rebagliati Martins 2009-2014 - Fernández Sierra, Carmen (2017)
Objective: The purpose of this study is to describe the neurodevelopmental sequelae in premature newborns with extremely low weight and with very low weight at two years of age who left the Neonatal Intensive Care Unit of the Hospital Nacional Edgardo Rebagliati Martins. Materials and methods: A descriptive, retrospective, cross-sectional study in a population of 190 premature newborns with extremely low weight and with very low weight born from January 2009 to June 2014 who left the Neonatal Intensive Care Unit and took part in the follow-up program. The psychomotor development, sensorineural hearing loss, retinopathy of prematurity, presence of cerebral palsy and convulsive syndrome were assessed. Results: The average weight at birth was 1,180.53 ± 212.40 grams with a gestational age of 29.86 ± 2.33 weeks, and 51.58% of the newborns were male. Forty-two point six three percent (42.63%) of the premature newborns with very low weight showed retardation of psychomotor development; 25.26%, retinopathy; 13.68%, sensorineural hearing loss; 3.68%, cerebral palsy; and 3.68%, convulsive syndrome. Fifty-two point two seven percent (52.27%) of the premature newborns with extremely low weight showed retardation of psychomotor development; 50%, retinopathy; 15.91%, sensorineural hearing loss; and 2.27%, convulsive syndrome. Conclusions: Retardation of psychomotor development and retinopathy were the most important complications shown by premature newborns with extremely low weight and with very low weight at two years of age.